Effect of plasma treatment on multilayer graphene: X-ray photoelectron spectroscopy, surface morphology investigations and work function measurements - Patil, Urmila V.; Pawbake, Amit S.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Jadkar, Sandesh R.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report here the effect of plasma treatment on multilayer graphene samples as determined by X-ray photoelectron spectroscopy and surface morphology studies with atomic force microscopy, scanning electron microscopy and transmission electron microscopy. The plasma treatment was modified to introduce controlled levels of defects and functionalities to the graphene samples to give tunable properties. The elemental composition and structure were investigated by XPS and micro Raman spectroscopy. The XPS study showed that there was a slight variation in the sp(2)/sp(3) hybridization ratio between the plasma-treated samples and the pristine sample. Kelvin probe measurements were carried out on all the multilayer graphene samples and indicated a slight variation in the work function of the graphene samples after plasma treatment.